Collaboration and Distribution of Leadership: Keys for Improvement in Chile's Vocational and Training Education (Práxis Educativa, 2024)
The purpose of this article is to examine the collaborative practices, distributed leadership patterns and collaborative culture in three secondary vocational technical education centers in Chile, which show a sustained trajectory of school improvement. For the examination of collaborative practices, semi-structured interviews were conducted with managers and focus groups with heads of departments, heads of specialties and teachers of general and differentiated education, and the Social Network Analysis questionnaire (SNA) was applied. For the identification of distributed leadership patterns, the Multidimensional Questionnaire of Distributed Leadership (CMLD) was applied. It is concluded that in the three cases studied there is a high valuation of collaborative work and distributed leadership practices in their management. Likewise, both managers and teachers show a tendency to think of improvement as a joint process.Keywords: Distributed leadership. Collaborative culture. School improvement.